2019
DOI: 10.21873/anticanres.13894
|View full text |Cite
|
Sign up to set email alerts
|

Development of Normal Tissue Complication Probability Model for Trismus in Head and Neck Cancer Patients Treated With Radiotherapy: The Role of Dosimetric and Clinical Factors

Abstract: following eligibility criteria: 1) HNC originating in the oral cavity, nasopharynx, oropharynx, hypopharynx, or larynx; 2) treated with definitive RT either alone or in combination with chemotherapy or cetuximab; 3) no previous surgery, RT and/or chemotherapy; 4) no previous malignancies; 5) no distant metastases; 6) planningcomputed tomography (CT) and three-dimensional dose distributions available prior to and 6 months after completion of (CH)RT; 7) no efforts of reducing dose in potential organs at risks (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Since outcome of patients with locally advanced SCCHN require improvement, many preclinical and clinical studies have been conducted during recent years (17)(18)(19)(20)(21)(22). The prognoses of patients with SCCHN are particularly poor, if unresectable or incompletely resected.…”
Section: Discussionmentioning
confidence: 99%
“…Since outcome of patients with locally advanced SCCHN require improvement, many preclinical and clinical studies have been conducted during recent years (17)(18)(19)(20)(21)(22). The prognoses of patients with SCCHN are particularly poor, if unresectable or incompletely resected.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the biological dose of OARs might be different according to the corresponding alpha/beta ratio, which might translate to a different toxicity development; for example, in the case of hypofractionated/accelerated radiotherapy treatment schedules. Current NTCP models are not designed to include altered fractionation, nevertheless some studies investigated the fractionation effect [ 31 , 39 , 54 ] ( Supplemental Table ), whereas others did not [ 38 ]. Other studies showed the potential of improving NTCP models with the addition of baseline imaging biomarkers [ 33 , 55 , 56 ], which represent patient-specific tissue characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…DVH (Dose Volume Histogram) was used to delimitation of these structures was drawn on the planning computerized tomography scan in axial sections of 2mm every two sections. After delimitation of the anatomical structures, we calculated the minimum, average, and maximum radiation doses received by these structures [19].…”
Section: Design and Dose Parameters Of The Temporomandibular Joint An...mentioning
confidence: 99%